Answer:
x = 8
Step-by-step explanation:
6x - 5 = 5x + 3
6x - 5x = 3 + 5 (combining like-terms)
x = 8
Hope this helps!
Answer:
2.4166666666 (6 forever)
Step-by-step explanation:
16x^2-40x+25 Yes I know my phone is messed up but at least you got the answer
Answer:
13r²(2rs + 4r³ - 3s⁴)
Step-by-step explanation:
In equation 26r³s + 52r⁵ - 39r²s⁴;
The GCF of 26, 52, and 39 = 13
The GCF of r³, r⁵ and r² = r²
The GCF of s, (no "s"), and s⁴ = no "s" (Since one of the number doesn't have "s")
Now we can factor out 13r² from all three expressions;
26r³s + 52r⁵ - 39r²s⁴
=> <em>13r²(2rs) + 13r²(4r³) - 13r²(3s⁴)</em>
To factor it all together;
<u>13r²(2rs + 4r³ - 3s⁴)</u>
Hope this helps!